1324 DEVELOPMENT OF A M&M MEETING INTEGRATING THE SITUATIONAL JUDGEMENT REVIEW (SJR) FRAMEWORK IN A GERIATRIC DEPARTMENT. (16th January 2023) - Palmer-Jones, C; Zamfir, I; Stoian, I
Abstract: Introduction: The National Mortality Case Record Review Programme commissioned in 2016 aimed to improve the learning from deaths process. As part of this aim, several reports were published, which identified barriers in implementing the mortality review process. Mortality and Morbidity (M&M) meetings can be an important mechanism for removing these barriers, and while have been in place for a long time in surgical specialties, are only recently becoming more common in medical specialties. We have developed an innovative M&M meeting in our geriatric department to integrate Mortality case reviews with teaching and QI development. Methods: We created a standardised mortality data collection proforma, using the (SJR) framework as a template. During the development, feedback was obtained from consultants and juniors. Data was then collected using the proforma by trainees, and all mortality cases were then reviewed with consultant supervision, and specific cases were chosen for their educational benefit or requiring areas of improvement. Cases were then presented at the meeting. At the end of the meetings, an action plan was then created in collaboration with the consultant and juniors in the meeting to create a teaching plan or develop a QI project to help improve service. Results: From feedback gained, the M&M was well received, and has already helped improve training and delivery of end of life care and recognising the dying patient. There were several difficulties identified during the process such as incomplete medical records, time and lack of engagement from other team members due to work pressures. Conclusion: Mortality meetings are an essential part of junior doctor training and hospital clinical governance, often times underutilised. They can support quality improvement and professional learning, especially when facilitated by a standardised mortality review process.